Comparative Study between Propofol and Dexmedetomidine for Conscious Sedation in Patients Undergoing Outpatient Colonoscopy - Karanth, Harish (Anesth Essays Res, 2018)
INTRODUCTION: Colonoscopy is a mildly painful procedure requiring conscious sedation. Though propofol is a widely used anesthetic agent in day-care procedures due to its rapid onset and quick recovery has a drawback of requiring resuscitation maneuvers more often than the conventional methods. Dexmedetomidine, a newly introduced, highly selective α(2)-adrenergic receptor agonist possessing hypnotic, sedative, anxiolytic, sympatholytic, and analgesic properties with impressive safety margin, needs to be explored for use in conscious sedation for colonoscopy procedure among South Indian population. MATERIALS AND METHODS: A prospective randomized comparative study was conducted on patients aged between 25 and 60 years with the American Society of Anesthesiologist physical status classes I and II posted for colonoscopy under monitored anesthesia care. Study group was randomly divided into two groups and administered propofol and dexmedetomidine. The primary outcome variable was assessments of sedation scores between the two groups. Secondary outcome variables were pain score assessments, hemodynamic comparisons, and adverse events among the two groups. Appropriate statistical tests were applied to compare the findings. RESULTS: After comparisons between the two groups, we found that patients on dexmedetomidine had similar sedation score as that of patients on propofol. However, there was a significantly higher incidence of systemic hypotension. Requirement of rescue analgesia and adverse events and other hemodynamic fluctuation were similar in both the groups. CONCLUSION: We conclude that dexmedetomidine has similar efficacy as propofol for conscious sedation required during colonoscopy. Occurrence of systolic hypotension was, however, significantly more among the group receiving dexmedetomidine.